Analisis Cognitif Higher Order Thinking Skills (Hots) dan Lower Order Thinking Skills (Lots) Reading Comprehension Pada Buku Ajar Bahasa Inggris Kelas XII Kemendikbud 2018 - Pratama, Yoga; Pitaloka, Roro Meifi (PT. LANCAR MEDIA KOMUNIKASI, 2024)
In general, there are special package book practice questionsReading Comprehension adjusted to students' level of thinking so that it can help students improve critical thinking as one of the basic cognitive abilities as explained by Bloom's. The purpose of this research is to evaluate the practice questions in sectionReading Comprehension in the textbookEFL class 12. To find out what the contents of the practice questions in sectionReading Comprehensionalready in line with the achievement of the 2013 curriculum which emphasizes the ability to think at a high level(I.E.). Descriptive-qualitative is applied as a research method. By using a listchecklist Based on the revised Bloom's taxonomy theory update, researchers found thatLOTS contributed a figure of 60.9%, whileI MEANis 39.1%. The results of this research are that the textbooks issued by the Ministry of Education and Culture are still inadequate and do not meet the needs of grade 12 students. The questions in the books are dominated byLOTS. Researchers suggest to curriculum designers, book writers and publishers that in the future they can provide more adequate and effective teaching materials so that they can improve students' cognitive abilities